2013
DOI: 10.1007/s10620-013-2938-9
|View full text |Cite
|
Sign up to set email alerts
|

Reverse-Phase Protein Array Analysis to Identify Biomarker Proteins in Human Pancreatic Cancer

Abstract: Background Pancreatic cancer is the fourth leading cause of cancer death in the U.S. The high mortality rate of patients with pancreatic cancer is primarily due to the difficulty of early diagnosis and a lack of effective therapies. There is an urgent need to discover novel molecular targets for early diagnosis and new therapeutic approaches to improve the clinical outcome of this deadly disease. Aim we utilized the reverse-phase protein assay (RPPA) to identify differentially expressed biomarker proteins in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…43 In a large pancreatic cancer GWAS analysis, Wei and coworkers 44 screened a database of over 3,000 pancreatic cancer patients and consistently found that the G-protein coupled receptor signaling pathway was the most significant pathway to predict pancreatic cancer risk. Huang et al, 45 found that the AKT signaling protein was significantly over-expressed in pancreatic cancer compared to noncancerous tissues using reverse phase protein array. Indeed, we previously demonstrated that growth of pancreatic cancer is regulated by the over-expression of this GPCR, CCK-BR 21 and that down regulation of the CCK-BR in pancreatic cancer cells results in apoptosis and halts cell proliferation 22 by interference with intracellular signaling and decreased AKT phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…43 In a large pancreatic cancer GWAS analysis, Wei and coworkers 44 screened a database of over 3,000 pancreatic cancer patients and consistently found that the G-protein coupled receptor signaling pathway was the most significant pathway to predict pancreatic cancer risk. Huang et al, 45 found that the AKT signaling protein was significantly over-expressed in pancreatic cancer compared to noncancerous tissues using reverse phase protein array. Indeed, we previously demonstrated that growth of pancreatic cancer is regulated by the over-expression of this GPCR, CCK-BR 21 and that down regulation of the CCK-BR in pancreatic cancer cells results in apoptosis and halts cell proliferation 22 by interference with intracellular signaling and decreased AKT phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…The RPPA method allows the measurement of protein expression levels and their post-translational states (cleavage, phosphorylation, ubiquitination) in a low volume of sample. RPPA has already been used to demonstrate the importance of several proteins and their post-translational modification in tumorogenesis [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…As previously discussed [8], reverse phase protein arrays discovered that GAB2, AKT, β-catenin and PAI-1 were overexpressed in pancreatic cancer [21]. In order to find articles with information about the proteins under investigation, queries are formulated with protein synonyms and aliases using logical notation.…”
Section: Standardized Knowledge Representation Formatmentioning
confidence: 99%